THE USE OF NEW INNOVATIVE TECHNIQUES IN TEACHING INFORMATION TECHNOLOGY TO STUDENTS IN THE FIELD OF PHARMACY (Proceedings of International Conference on Modern Science and Scientific Studies, 2023)
This article provides recommendations for the use of new methods in teaching information technology to students in the field of Pharmacy of medical institutes.